Integrated Technology In Learning Viewed From The Lens 0f 21st Century Education: A Qualitative Study On Teacher’s Efforts In Improving Islamic Education Quality - RN, Bustanul Iman; Nuris, Masdiyah; Syaripuddin, Rahmatullah (Sekolah Tinggi Agama Islam Al Hidayah, 2023)
The study discusses the efforts made by Islamic religious education (PAI) teachers to use ICT-based learning media, the use of information and communication technology-based learning media in PAI learning, and the quality of Islamic religious education. The type of the research was a descriptive qualitative study at a public junior high school in Soreang District, Parepare City. The data used were primary and secondary. The research instruments were observation, interview, and documentation guidelines. The research data was obtained through observation, interviews, and documentation. The results showed several efforts carried out by PAI teachers, namely preparing the lesson plan, selecting, and designing the media devices according to the religious education materials, using learning media based on information and communication technology, opening the teaching and learning activities by greeting and praying together, presented learning materials with various media, formed a study group by giving a problem needed to be solved from the observations of the films, videos, music, and images presented, discussed materials to find answers to the problems shown, provided confirmation or explanation and reinforcement of the results of the discussion of the material presented, and ended the class by saying hamdalah and greetings.